An unusual cause of food-induced anaphylaxis in mothers. Issue 1 (December 2017) - Soh, J.; Chiang, W.; Huang, C.; Woo, C.; Ibrahim, I.; Heng, K.; Pramanick, A.; Lee, B.
Abstract Background Galacto-oligosaccharides (GOS) are prebiotics added to commercial milk formula of infants and mothers. In recent years, cases of allergy related to GOS in atopic children have been reported in the South East Asian region. Case presentations We describe a series of pregnant (n  = 4) and lactating mothers (n  = 2) who developed anaphylactic reactions after consumption of maternal milk formula containing GOS. All six subjects had pre-existing atopy and a positive skin prick test to GOS and 5/5 of the subjects who were tested had positive basophil activation tests to GOS. All of the mothers and their babies had normal neonatal outcomes after the reactions. Conclusions The supplementation of GOS into milk and beverages in the Asian region should take into account the rare chance of allergenicity of GOS in the atopic population.